Implementation of Facial Visualization of MBTI Personality Type Based on Augmented Reality and Dynamic Mapping - Hee Lee, Kang; Ganiev, Asilbek (International Journal of Engineering and Technology, 2018)
Nowadays, augmented reality is becoming more and more popular because it can help individuals learn about many things, such as buildings, books, historical places, etc. in real time. The Myersâ€“Briggs Type Indicator (MBTI) test, a questionnaire-based test, is used to determine personality type, which influences perceptions of the world and the ways in which individuals make decisions. This system is based on C.G Jungâ€™s typological theory and was developed by Katherine and Isabel Briggs.Â Â Â Â The purpose of this paper is to use the MBTI personality test to define the personality types of users. To accomplish this aim, we used Unity3D, Processing, and Vuforia SDK. First, the processing program was used to produce results from sixteen images and send them to Unity3D. Second, Vuforia SDK was used to recognize masks in real time and map images to the masks. Then, Unity3D displayed the final mapping result.Â Â